Reduced aggrecan expression affects cardiac outflow tract development in zebrafish and is associated with bicuspid aortic valve disease in humans. (15th December 2017) - Rambeau, Pierre; Faure, Emilie; Théron, Alexis; Avierinos, Jean-François; Jopling, Chris; Zaffran, Stéphane; Faucherre, Adèle
Abstract: Hemodynamic forces have been known for a long time to regulate cardiogenic processes such as cardiac valve development. During embryonic development in vertebrates, the outflow tract (OFT) adjacent to the ventricle comes under increasing hemodynamic load as cardiogenesis proceeds. Consequently, extracellular matrix components are produced in this region as the cardiac cushions form which will eventually give rise to the aortic valves. The proteoglycan AGGRECAN is a key component of the aortic valves and is frequently found to be deregulated in a variety of aortic valve diseases. Here we demonstrate that aggrecan expression in the OFT of developing zebrafish embryos is hemodynamically dependent, a process presumably mediated by mechanosensitive channels. Furthermore, knockdown or knockout of aggrecan leads to failure of the OFT to develop resulting in stenosis. Based on these findings we analysed the expression of AGGRECAN in human bicuspid aortic valves (BAV). We found that in type 0 BAV there was a significant reduction in the expression of AGGRECAN . Our data indicate that aggrecan is required for OFT development and when its expression is reduced this is associated with BAV in humans. Highlights: The proteoglycan Aggrecan is expressed in the zebrafish outflow tract during cardiac development. Aggrecan expression in the outflow tract is dependent on hemodynamic forces. AGGRECAN expression is reduced in human type 0 bicuspid aortic valves.